A study on the antihyperglycemic effect of aqueous extract of Sida rhombifolia leaves on blood glucose level of experimental animals - Devi, Laitonjam Jonita; Raleng, Indira; Devi, Laishram Elizabeth; Singh, Oinam Joychandra (International Journal of Research in Medical Sciences, 2026)
Background: Medicinal plants are used for the treatment of many ailments. Sida rhombifolia which has various medicinal properties is investigated for its effects on blood glucose level of the experimental animals. Methods: The cleaned dried leaves of Sida rhombifolia was Soxhlet with water for Sida rhombifolia extract (SRE). 53 albino rats were recruited. Acute toxicity test was done by administering up to the dose of 2000 mg/kg to 5 albino rats but no toxicity was observed. The SRE at the doses of 200 mg/kg, 400 mg/kg were administered orally at 0 hour, ½ hour, 1 hour and 2 hours to 24 normal rats. Similarly, the standard drug metformin (0.5 mg/kg) was also administered orally. The blood glucose levels (BGL) of the rats were estimated. Then the same doses of SRE and metformin were administered orally to 24 diabetic induced rats at the same point of time. The BGLs of the diabetic rats were estimated. The MBGLs of the diabetic rats after administration of the extract and standard were compared to the MBGLs of the diabetic control. Results: The effect of the extract of BGLs of the diabetic rats were found to be statistically significant. But the observation on the comparison of the MBGLs of the standard and diabetic control was insignificant. Since the SRE contains phytochemicals like flavonoids, its probable mechanism of action is increasing of sensitivity of insulin or act as an insulin secretagogue. Conclusions: Therefore, SRE may have antihyperglycemic property.